EXVOTO (VOTIVE OFFERING) OF THE SANTA CATARINA DE SIENA CHURCH IN VALLADOLID. SIGLO XVIII. (Tzintzun, Revista de Estudios Históricos, 2016)
This article analyses a big votive offering which is located on the high choir of SantaCatalina de Sienna church in Morelia, better known as “Las Monjas” (The Nuns).The painting shows the nuns’ daily life and the activities they were performingwhen a spark got into the choir window without hurting them. To analyze thepainting the social and religious context have been taken into consideration so thatpeople can access that time way of thinking. An iconographic analysis has also beenmade to identify the different elements that the painting has and their meaning. Aformal study has been made in order to learn the technical aspects of the paintingwhich shows the composition, the lightening, the rhythm, the color and the skilledused of the brush. The votive offering is related to the Dormicion Virgin devotion.
Keywords: Votive offering; dormición virgin; dormicion iconography; Santa Catarina de Siena; Valladolid Nueva España